Measurement report: Size-resolved particle effective density measured by an AAC-SMPS and implications for chemical composition - Y. Song; J. Wei; W. Zhao; J. Ding; X. Pei; F. Zhang; Z. Xu; R. Shi; Y. Wei; L. Zhang; L. Jin; Z. Wang; et al. (Atmospheric Chemistry and Physics)
The effective density (ρeff) is closely associated with the aging process and can serve as a tracer of chemical composition. Recently, studies investigating the effect of particle size on density have been limited. In this study, size-resolved ρeff was characterized using a tandem aerodynamic aerosol classifier (AAC) and scanning mobility particle sizer (SMPS) system during 1 month of observations in Hangzhou. The results indicate that the ρeff values of the particles exhibit a unimodal distribution, with average values ranging from 1.47 to 1.63 g cm−3, increasing as the particle diameter increases. The diurnal variation is more pronounced for small particles (dae < 350 nm), which generally exhibit lower density during the day and higher density at night. The relationship between ρeff and particle diameter varies under different pollution conditions due to differences in the chemical composition of the particles. The SHapley Additive exPlanations (SHAP) values revealed good relationships between ρeff and the bulk composition of particles with diameters smaller than 350 nm, while the relationship with larger particles was weak. As determining the size-resolved chemical composition of particles remains challenging, a new method to investigate the size-resolved chemical composition was proposed, in which the size-resolved composition can be derived from the ρeff and fixed material density of secondary inorganic aerosols (SIAs), organic aerosols (OAs), and black carbon (BC).